Variations in Pakistan’s Policy of Neutrality during the Middle Eastern Conflicts - Ali, Muhammad Irfan; Khan, Waheed Ahmad; Adnan, Malik (Annals of Human and Social Sciences, 2024)
Pakistan has a proclaimed policy of neutrality towards Middle Eastern politics due to the rivalry between Saudi Arabia and Iran. By explaining the multiple factors behind Saudi-Iran rivalry this research article would measure the scale of neutrality in Pakistan’s foreign policy towards Middle East. By adopting the John Scot’s model of Documentary analysis in qualitative research, the researcher has designed a criterion of analyzing the neutrality in Pakistan’s foreign policy towards Middle East. As, there are multiple indicators of neutrality that can help in measuring Pakistan’s position of neutrality towards Saudi-Iran rivalry in Yemen, Syria, and Iraq. To explain variation in Pakistan’s policy of neutrality, we employ theoretical perspectives of realism and constructivism that helped us to systemically study this variation by factoring in domestic, regional, and international factors. Through this analysis, it was found that even though, mainly due to its identity as a Sunni-majority country, Pakistan tilts towards Saudi-backed bloc of Sunni states, it also tries to appease Iran and its allies for security and economic reasons. This situation requires Pakistan to stay neutral during Middle Eastern conflicts. However, regional, and international pressures compel it to relax this policy. As each conflict has unique regional and international dynamics, Pakistan adjusts its policy of neutrality to ensure its security and to gain maximum economic benefits.